2007
DOI: 10.1093/humrep/del479
|View full text |Cite
|
Sign up to set email alerts
|

Influence of endogenous and exogenous sex hormones on plasma brain-derived neurotrophic factor

Abstract: Plasma BDNF levels are influenced by hormonal status. Modifications in BDNF circulating levels during the menstrual cycle suggest a potential role for gonadal sex hormones (E(2) and progesterone) in regulating neurotrophin expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
143
4
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 212 publications
(165 citation statements)
references
References 43 publications
13
143
4
1
Order By: Relevance
“…This study showed that the BDNF was positively correlated with E 2 , a finding consistent with previous studies [15,18]. Increasing evidence showed the synthesis of BDNF was positively correlated with the synthesis of estrogen.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study showed that the BDNF was positively correlated with E 2 , a finding consistent with previous studies [15,18]. Increasing evidence showed the synthesis of BDNF was positively correlated with the synthesis of estrogen.…”
Section: Discussionsupporting
confidence: 92%
“…In the study, there was no relationship between BDNF and P in FF. However, Begliuomini et al [18] demonstrated that the level of BDNF was positively correlated with P in fertile women. Chen et al [20] found BNDF significantly inhibited the production of P in a dose-dependent manner when they cultured human granulose-lutein cells in medium without or with different dosage of BDNF.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies in mice (Advani et al., 2009; Ren‐Patterson et al., 2006) and in humans (Shalev et al., 2009; Verhagen et al., 2010) have shown a sex difference in the effect of BDNF. This difference may be related to the interactions between BDNF and sex hormones such as estradiol (Begliuomini et al., 2007; Sohrabji et al., 1995) and testosterone (Hill et al., 2012; Verhovshek et al., 2010). Another explanation for the sex difference in the interaction effect might lie in the lower variability found for maternal warmth compared to paternal warmth.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the val66met polymorphism of the BDNF gene affects the onset of multiple sclerosis (MS) only in men and increases the risk of MS only in women (Mirowska‐Guzel, Mach, Gromadzka, Czlonkowski, & Czlonkowska, 2008). These differences may be explained by interactions between BDNF and sex hormones such as estradiol (Begliuomini et al., 2007; Sohrabji, Miranda, & Toran‐Allerand, 1995) and testosterone (Hill, Wu, Kwek, & van den Buuse, 2012; Verhovshek, Cai, Osborne, & Sengelaub, 2010). In rats, estrogen has been shown to regulate BDNF mRNA levels, possibly via an estrogen response element on the BDNF gene (Sohrabji et al., 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation